Do beliefs in the model minority stereotype reduce attention to inequality that adversely affects Asian Americans? - Shuai Chen; Nattavudh Powdthavee; Juliane Wiese (Global Labor Organization (GLO), 2024)
We study whether the model minority stereotype about Asian Americans (e.g., hard-working, intelligent) reduces people's attention to inequality that adversely affects Asians. In a nationally representative US sample (N=3,257), we find that around 90% of the participants either moderately or strongly believe that Asians work harder and are more economically successful compared to other ethnic minorities. We then demonstrate that an increase in the model minority belief has a dose-response relationship with people's tendency to overestimate incomes for Asians but not for Whites and Blacks. In a basic cognitive task, people are more likely to see an equal distribution of resources between Asians and people of other races when Asians have less than others by design. Although there is little evidence that a marginal increase in the model minority belief significantly reduces people's attention to inequality that adversely affects Asians in a pattern detection hiring task, we find that people who hold a strong model minority stereotype are only more likely to naturalistically point out unfair hiring practices when Whites are discriminated against. Our results offer new insights into the possible mechanisms behind why many Americans are relatively more apathetic toward Asians' unfair treatment and negative experiences compared to those of other races.
Keywords: D63; D91; J15; 330; Asian Americans; model minority; stereotype; inequality; attention; redistribution